Role of Financial Literacy and Saving Habits on Fintech Adoption post Covid-19 - Deni Pandu Nugraha; Budi Setiawan; Emilda Emilda; Muhammad Masyhuri; Mac Nhu Quynh; Robert Jeyakumar Nathan; Maria Fekete‐Farkas; István Hágen (ETIKONOMI, 2024)
Research Originality: This research paper enriches existing literature on drivers of fintech adoption, including the impact of perceived trust, individual innovativeness, savings habits, and government support on Indonesian users' post-COVID-19 pandemic fintech adoption intentions.Research Objectives: This study examines the impact of post-covid changes in people's behaviour, savings habits and accelerated financial literacy on strengthening Technology Adoption Model (TAM) among Indonesian fintech users. Research Methods: The researchers surveyed 536 people living in Indonesia. The data was analysed using structural equation modelling with moderator variables. Empirical Results: It found that ease of use, usefulness, trust and personal innovativeness are key drivers of adoption intentions. The research also found that savings habits significantly increase the influence of government support on fintech adoption. Implications: This research has two important implications. First, digital finance companies should further improve fintech app service quality and security. Second, the government should also encourage the expansion of a fintech-based startup ecosystem by providing regulatory support to accelerate the progress of Indonesia's digital finance industry.JEL Classification: M21, G23, O36How to Cite:Nugraha, D. P., Setiawan, B., Emilda, E., Masyhuri, M., Quynh, M. N., Nathan, R. J., Fekete-Farkas, M., & Hagen, I. (2024). Role of Financial Literacy and Saving Habits on Fintech Adoption post Covid-19. Etikonomi, 23(1), 63 – 80. https://doi.org/10.15408/etk.v23i1.37856.